Study of associated root cause of mal- tripping and the environmental effect in arc flash protection system air insulated switchgear - Mohd Nur Khaidir Hussein (2023)
This thesis presents the establishment of associated root cause of mal-tripping in arc flash protection system. This study related to the arc flash protection system that has been used in Tenaga Nasional Berhad (TNB) and has been proven a fast acting fault isolation system